2001
DOI: 10.2134/agronj2001.932468x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Swards Containing Forage Chicory

Abstract: value of chicory herbage and to identify nutrient inputs that sustain production, especially when high rates of Chicory (Cichorium intybus L.), a highly productive forage under N are applied. Crush and Evans (1990) and Reid et al. midsummer conditions in the eastern USA, often has higher concentrations of minerals relative to grasses and legumes. Low concentra- (1993) reported that the mineral composition of forage tions of minerals in herbage could reduce production efficiency or chicory was comparable to or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 20 publications
(45 reference statements)
6
41
4
Order By: Relevance
“…In the current experiment, ryegrass had a total P content in the tops of 7287 mg kg -1 DM. Belesky et al (2001) reported P contents of 4400 mg kg -1 in a young crop of chicory and 3700 mg kg -1 in an older crop, whereas in the current experiment, chicory was 7305 mg kg -1 . These other values indicate that in comparison, the P concentrations in plants from this study were higher.…”
Section: Phosphorus Leaching From the Plant-only Experimentscontrasting
confidence: 74%
“…In the current experiment, ryegrass had a total P content in the tops of 7287 mg kg -1 DM. Belesky et al (2001) reported P contents of 4400 mg kg -1 in a young crop of chicory and 3700 mg kg -1 in an older crop, whereas in the current experiment, chicory was 7305 mg kg -1 . These other values indicate that in comparison, the P concentrations in plants from this study were higher.…”
Section: Phosphorus Leaching From the Plant-only Experimentscontrasting
confidence: 74%
“…Increasingly it is appreciated that additional species may profoundly affect ecosystem functions and provisional services (Naeem et al, 1995;Vitousek et al, 1997;Belesky et al, 2001;Høgh-Jensen et al, 2006;Gylfadó ttir et al, 2007). Management optimization of temporary grassland systems, which are only kept for a few years (Allen et al 2011) must take species traits and soil fertility into consideration (Whitehead et al, 1978;Hopkins et al, 1994).…”
Section: G Kgmentioning
confidence: 99%
“…However, many pasture plants supply other elements that influence the performance of those ingesting the herbage. Belesky et al (2001) investigated mineral composition in pure stand chicory and Whitehead et al (1978) in pure stand ryegrass but studies in mixtures have also been reported (Whitehead et al, 1983, Lawes & Gilbert, 1990, Hopkins et al, 1994. Hopkins et al (1994) described the variation in selected macro-and micro-mineral concentrations in Lolium perenne/Trifolium repens-dominated swards over seasons and over years (Hopkins et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is native to Europe, Western and Central Asia, North Africa and South America and is after intensive breeding efforts gaining popularity in grassland due to its high forage quality and productivity (Barry, 1998;Belesky et al, 2001;Collins and McCoy, 1997).…”
Section: Introductionmentioning
confidence: 99%